Environmental impacts of cold chain distribution operations: a novel portable refrigerated unit. Issue 2 (2018) - Ferretti, Ivan; Mazzoldi, Laura; Zanoni, Simone
This paper presents a model for the evaluation of the environmental impacts associated with the management of cold supply chain, considering transport and storage activities. A novel portable refrigerated unit (PRU) for the management of goods along the cold chain is presented, and its performances, in terms of emissions at different distribution stages, are compared to those of traditional cold chain equipment. A mathematical model based on costs and environmental impacts has been developed. Moreover, a case study is presented so as to show the usefulness of the model proposed. Numerical analyses are provided in order to demonstrate the efficiency of the new equipment, compared to the traditional refrigeration technology involved in distribution chains. Environmental benefits and efficiency of the new equipment are considered, as well as energy consumption reduction. The proposed system may help companies to pursue more sustainable practices in their cold chain activities.